(untitled) (International Journal of Ecophysiology, 2023)
Typhoid fever is a digestive tract infection caused by Salmonella typhi. Treatment of typhoid fever can use natural ingredients such as lime peel waste. The purpose of this study was to determine the effect of the ethanol extract of lime peel waste on the growth of Salmonella typhi bacteria. The extraction method used the maceration technique, and the antibacterial activity test used the paper disc diffusion method. The results showed that the ethanol extract of lime peel waste at concentrations of 1 mg/ml, 3 mg/ml, 5 mg/ml and 7 mg/ml with inhibition zone diameters of 4.66 mm, 6.55 mm, 9.29 mm and 10.06 mm. The conclusion shows that there is an effect of lime peel ethanol extract in inhibiting the growth of Salmonella typhi bacteria in the weak to strong category.